Hip and trunk neuromuscular training to reduce risk of ACL injury in sport: Responders and nonresponders in elite female team sport athletes - Weir, G. J.; Cantwell, D.; Alderson, J. A.; Elliott, B. C.; Donnelly, C. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The aim of this study was to determine if body-weight based (BWB) neuromuscular training targeting the hip and trunk is effective in altering the activation of the muscles crossing the hip and knee, reducing peak knee joint loading and anterior cruciate ligament (ACL) injury risk among elite female field hockey players. A secondary objective was to determine if all athletes within this cohort responded in a similar manner to training, or when clustered into sub-groups based on response to training (i.e. reductions in peak knee loading) displayed unique biomechanical and/or neuromuscular adaptations that could explain these differences. Methods: Sixteen elite female hockey players participated in eight weeks of BWB neuromuscular training, targeting the hip and trunk. Hip, knee and ankle moments, support moment and the activation of nine lower limb muscles were calculated during weight acceptance of unplanned sidestepping prior to, and following training. Athletes were then classified as `responders` (n=4) and `non-responders` (n=12).Total muscle activation (TMA) of all lower limb muscles and individual muscle groups (gluteal, quadriceps, hamstrings and gastrocnemii) were calculated. A split-plot ANOVA was used to assess changes in lower limb kinetics (á=0.05) and Cohen`s d for muscle activation changes following training. Results: As a group (n=16), no differences in lower limb kinetics were observed. Responders displayed reductions in peak knee valgus (-28%; p=0.003) and extension (-10%; p=0.005) moments following training, and interestingly displayed higher peak knee valgus moments relative to non-responders prior to training. No change in support moment existed pre to post training for both groups, however an increase in peak hip extension moments (+18%; p=0.046) were observed in responders. A large effect was observed for increased TMA-gluteal for responders (+29%; d=1.4). Discussion: Following hip and trunk focused BWB neuromuscular training, responder athletes better utilized their hip musculature to generate their support moment. This is thought to be related to the reduced peak extension and valgus moments observed at the knee, therefore effectively reducing ACL injury risk (Donnelly et al., 2012; Markolf et al., 1995). The analysis of responding athletes is important for improvement of the effectiveness of injury prevention protocols (Myer et al., 2007).